The Role of a Dipeptide Transporter in the Virulence of Human Pathogen, Helicobacter pylori - Xu, Xiaohong; Chen, Junwei; Huang, Xiaoxing; Feng, Shunhang; Zhang, Xiaoyan; She, Feifei; Wen, Yancheng (Frontiers in Microbiology, 2021)
Helicobacter pylori harbors a dipeptide (Dpp) transporter consisting of a substrate-binding protein (DppA), two permeases (DppB and C), and two ATPases (DppD and F). The Dpp transporter is responsible for the transportation of dipeptides and short peptides. We found that its expression is important for the growth of H. pylori. To understand the role of the Dpp transporter in the pathogenesis of H. pylori, the expression of virulence factors and H. pylori-induced IL-8 production were investigated in H. pylori wild-type and isogenic H. pylori Dpp transporter mutants. We found that expression of CagA was downregulated, while expression of type 4 secretion system (T4SS) components was upregulated in Dpp transporter-mutants. A DppA mutant strain expressed higher levels of outer membrane proteins (OMPs), including BabA, HopZ, OipA, and SabA, and showed a higher adhesion level to gastric epithelial AGS cells compared with an H. pylori 26695 wild-type strain. After infection of AGS cells, ΔdppA cells induced a higher level of NF-κB activation and IL-8 production compared with infection with wild-type cells. These results suggest that the Dpp transporter not only is important for the growth of H. pylori but also causes bacteria to alter the expression of virulence factors and reduces H. pylori-induced NF-κB activation and IL-8 production in gastric epithelial cells.